2023
DOI: 10.1128/spectrum.02910-23
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis at three oral sites links oral microbiota to clinical outcomes in allogeneic hematopoietic stem-cell transplant

Vitor Heidrich,
Franciele H. Knebel,
Julia S. Bruno
et al.

Abstract: Allogeneic hematopoietic stem-cell transplant (allo-HSCT) is potentially curative for several hematological disorders. Before stem-cell infusion, recipients undergo a conditioning regimen with chemo/radiotherapy and immunosuppressants, requiring the use of antibiotics to treat and prevent infections. This regimen promotes drastic alterations in the recipient’s microbiota, including the oral microbiota, which have been associated with allo-HSCT complications and poor outcomes. However, long-term longitudinal st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…This study aims to investigate the changes in the microbiome of the oral and intestinal microbiomes in pediatric patients who underwent allogeneic HSCT. The study found that the toxic effects of different conditioning regimens used during HSCT can lead to microbial dysbiosis in various environments, including the oral cavity 23 . www.nature.com/scientificreports/ This can result in the development of infectious and immunological complications in patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to investigate the changes in the microbiome of the oral and intestinal microbiomes in pediatric patients who underwent allogeneic HSCT. The study found that the toxic effects of different conditioning regimens used during HSCT can lead to microbial dysbiosis in various environments, including the oral cavity 23 . www.nature.com/scientificreports/ This can result in the development of infectious and immunological complications in patients.…”
Section: Discussionmentioning
confidence: 99%